2001
DOI: 10.1038/sj.bmt.1702830
|View full text |Cite
|
Sign up to set email alerts
|

Human γδ+ T lymphocytes have in vitro graft vs leukemia activity in the absence of an allogeneic response

Abstract: Summary:Refractory acute lymphoblastic leukemia (ALL) is often incurable, and relapse rates following allogeneic bone marrow transplantation (BMT) remain high. We have reported that patients who develop increased numbers of ␥␦ + T cells soon after BMT are significantly less likely to relapse. We now show in seven donor/recipient pairs that donor-derived V␦1 + CD4 − CD8 − ␥␦ + T cells are activated and proliferate in response to recipient primary ALL blasts. In addition, these cells have been shown to bind and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 18 publications
4
83
0
Order By: Relevance
“…Ten of forty-three patients had increased peripheral blood gd T cell counts at 60-270 days after BMT, and all remained alive and free of disease at 2.5 years compared with a disease-free survival probability of 31% among patients with nonelevated gd T cell counts. The same group later showed that enrichment of the marrow graft with gd T cells decreases the incidence of relapse, and that gd T cells proliferate in vitro in response to acute lymphoblastic leukemia (ALL) blasts (61). Thus, they suggested a possible association between an increase in the number of gd T cells and improved disease-free survival.…”
Section: Flow Cytometric Assessment Of CD T Cells In Amlmentioning
confidence: 85%
See 3 more Smart Citations
“…Ten of forty-three patients had increased peripheral blood gd T cell counts at 60-270 days after BMT, and all remained alive and free of disease at 2.5 years compared with a disease-free survival probability of 31% among patients with nonelevated gd T cell counts. The same group later showed that enrichment of the marrow graft with gd T cells decreases the incidence of relapse, and that gd T cells proliferate in vitro in response to acute lymphoblastic leukemia (ALL) blasts (61). Thus, they suggested a possible association between an increase in the number of gd T cells and improved disease-free survival.…”
Section: Flow Cytometric Assessment Of CD T Cells In Amlmentioning
confidence: 85%
“…AML relapse is assumed to arise from minimal residual disease (64). T cell immunosurveillance of residual leukemia may help to achieve durable remissions (61). Prolonging event-free survival of AML with immune cells, such as gd T cells, is therefore a promising concept and is under investigation by our group.…”
Section: Flow Cytometric Assessment Of CD T Cells In Amlmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, as for some other non-conventional T cell subsets, the antigenic activation process of Vg9Vd2 T cells is TCR-and contact-dependent, involving the expression of key molecules (eg., PAg and butyrophilins), 29 but not restricted by MHC class I/II molecules, then eliminating any risk of deleterious direct alloreactive responses toward non-transformed cells. 30,31 Therefore, the constitution of clinical allogeneic human Vg9Vd2 T cell banks, established from healthy donors, could represent a unique opportunity for designing adoptive transfer antitumor immunotherapies. Administration of effector T cells could be further hampered by the particular immunological status of the central nervous system, notably characterized by the presence of the bloodbrain barrier (BBB) and the absence of classical lymphatic drainage system, 32,33 then limiting T cell trafficking within the brain parenchyma and representing an additional obstacle to intravenous injections.…”
Section: Discussionmentioning
confidence: 99%